Fabrication of Pamidronic Acid-Immobilized TiO2/Hydroxyapatite Composite Nanofiber Mats for Biomedical Applications. (30th December 2013) - Shin, Yong-Suk; Borah, Jyoti S.; Haider, Adnan; Kim, Sukyoung; Huh, Man-Woo; Kang, Inn-Kyu
Abstract : TiO2 /hydroxyapatite (TiO2 /HA) composite nanofiber mats were fabricated using an electrospinning technique. Subsequently, pamidronic acid (PDA) was immobilized on the surface of the TiO2 /HA nanofiber mat to improve osseointegration. X-ray photoelectron microscopy and scanning electron microscopy (SEM) were used to characterize the structure and morphology of the PDA-immobilized TiO2 /HA composite nanofiber mat (TiO2 /HA-P). The potential of TiO2 /HA-P as a bone scaffold was assessed by examining the cell adhesion and proliferation of osteoblasts and osteoclasts. The adhesion and proliferation of osteoblasts on the TiO2 /HA-P composite nanofiber mat were slightly higher than those on the TiO2 /HA composite nanofiber mat, whereas the viability of osteoclasts on the TiO2 /HA-P nanofiber mat was significantly suppressed. These results suggest that the TiO2 /HA-P nanofiber mat has the potential for use as a therapeutic bone implant.